Regional security, ethnicity and governance : the challenges for South Asia - Richter, Justus; Wagner, Christian, 1958- (New Delhi : Manohar, 1998)
Contributed articles.
Keywords: National security -- South Asia; South Asia -- Ethnic relations; South Asia -- Politics and government